Ghana's maize market - Ministry of Food and Agriculture, Ghana; International Food Policy Research Institute; Amewu, Sena; Arhin, Eunice; Danso, Jane; Doughan, Roland Ato; Nafrah, Christiana; Owusu, Ivy; Pauw, Karl (International Food Policy Research Institute, 2020)
Maize is a widely consumed and cultivated staple crop in Ghana. It accounts for more than one-quarter of calories consumed, about double that of the second crop, cassava (GSS 2018). About three-quarters of maize consumption is from own production, suggesting maize has limited appeal as a cash crop (Gage et al. 2012). This is set to change as Ghana’s Planting for Food and Jobs (PFJ) initiative, launched in 2017, prioritizes maize seed and fertilizer distribution and encourages market participation by smallholders (MoFA 2019). Already average maize output over the period 2017 to 2019 has been 40 percent higher than the average output achieved between 2013 and 2016 (MoFA 2020a). Government attributes this dramatic production response to PFJ. It is uncertain whether the maize market in Ghana can absorb increased this increased maize output without significant impacts on market prices or the profitability of maize cultivation.